Understanding Ecological Hadiths With Interconnective Approaches in Responding to Ecological Problems - Nur Kholis; Qaem Aulassyahied (Universitas Ahmad Dahlan, 2022)
One of the global crises experienced by the world is the ecological crisis. Various kinds of natural disasters cannot be separated from the environmental damage that occurs cumulatively and collectively. Excessive use of technology and development that does not care about the environment can damage nature; as mentioned in Islam, preserving nature is one of the tasks of human beings. Scholars have written a lot regarding the concept of maintaining nature based on the Qur'an. However, this effort has not been thoroughly carried out on the hadith. This is evidenced in the discussion of the hadiths in classical fiqh books, which are more focused on the 'ubūdiyyah syar'iyyah aspect, such as the problem of tahārah. These hadiths have the potential to be understood more contextually and ecologically. Based on this, this paper tries to answer academic questions, how is the understanding of hadiths that can respond to the global ecological crisis? The author attempts to understand these traditions by the interconnective method to broaden the scope of meaning. The data used are the main books of hadith, books of hadith that explain from the fiqh perspective and some factual data regarding the ecological crisis. This paper aims to produce contextual meanings that respond positively to various environmental problems globally and locally.